Rola bezpieczeństwa informacji w przedsiębiorstwie w warunkach upowszechniania się Internetu - Galewski, Tomasz (The Role of Information Security in a Company in Terms of Internet Spreading, 2006)
The article takes up the problem of information security, which is crucial for companies nowadays. This issue has a big importance in terms of Internet spreading. Wide range of Internet appliances results in many changes in company's activities. The global network is a facilitation for information processes, but it also poses a threat for information security. The article mentions the most important aspects of information security and types of threats that appear in companies' information systems. Different kinds of attacks are divided into groups depending on their source and attacker's intentions. The author also assigns economical consequences of every mentioned type of attack. The last part of the article introduces basic rules of information security policy in a company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 138-152